Minimally Invasive Direct Coronary Artery Bypass in High-Risk Patients with Multivessel Disease - Hoffmann, Grischa; Friedrich, Christine; Huenges, Katharina; Petzina, Rainer; Vogt, Astrid-Mareike; Cremer, Joachim; Grothusen, Christina (The Thoracic and Cardiovascular Surgeon, 2021)
Background High-risk patients with multivessel disease (MVD) including a complex stenosis of the left anterior descending coronary may not be ideal candidates for guideline compliant therapy by coronary artery bypass grafting (CABG) regarding invasiveness and perioperative complications. However, they may benefit from minimally invasive direct coronary artery bypass (MIDCAB) grafting and hybrid revascularization (HCR).Methods A logistic European system for cardiac operative risk evaluation score (logES) >10% defined high risk. In high-risk patients with MVD undergoing MIDCAB or HCR, the incidence of major adverse cardiac and cerebrovascular events (MACCEs) after 30 days and during midterm follow-up was evaluated.Results Out of 1,250 patients undergoing MIDCAB at our institution between 1998 and 2015, 78 patients (logES: 18.5%; age, 76.7 ± 8.6 years) met the inclusion criteria. During the first 30 days, mortality and rate of MACCE were 9.0%; early mortality was two-fold overestimated by logES. Complete revascularization as scheduled was finally achieved in 64 patients (82.1%). Median follow-up time reached 3.4 (1.2–6.5) years with a median survival time of 4.7 years. Survival after 1, 3, and 5 years was 77, 62, and 48%.Conclusion In high-risk patients with MVD, MIDCAB is associated with acceptable early outcome which is better than predicted by logES. Taking the high-risk profile into consideration, midterm follow-up showed satisfying results, although scheduled HCR was not realized in a relevant proportion. In selected cases of MVD, MIDCAB presents an acceptable alternative for high-risk patients.
Keywords: coronary artery bypass grafts surgery; CABG; minimally invasive surgery, includes port access minithoracotomy; outcomes, includes mortality morbidity